EfGD: the Erianthus fulvus genome database. (31st August 2022) - Qian, Zhenfeng; Li, Xuzhen; He, Lilian; Gu, Shujie; Shen, Qingqing; Rao, Xibing; Zhang, Rongqiong; Di, Yining; Xie, Linyan; Wang, Xianhong; Chen, Shuying; Dong, Yang; et al.
Abstract: Erianthus fulvus (TaxID: 154759) is a valuable germplasm resource in sugarcane breeding and research and has excellent agronomic traits, such as drought resistance, cold resistance, barren tolerance and high brix. With a stable chromosome number (2 n = 20) and a small genome (0.9 Gb), it is an ideal candidate for research on sugarcane. Next-generation sequencing technology has enabled a growing number of studies to focus on genomics. Due to the large amount of omics data available, a centralized platform is necessary for ensuring the consistency, independence and maintainability of these large-scale datasets through storage, analysis and integration. Here, we present a comprehensive database for the E. fulvus genome, EfGD. By using the new high-quality reference genome and its annotations, the EfGD provides the largest whole-genome sequencing reference dataset for E. fulvus, which archives 27 165 protein-coding genes and 55 564 488 SNPs from 202 newly resequenced genomes. Furthermore, we created a user-friendly graphical interface for visualizing genomic diversity, population structure and evolution and provided other tools on an open platform. Database URL : https://efgenome.ynau.edu.cn